Symptoms Experienced by Women at Home and Self-Care Agency after Breast-Conserving Surgery - (:unkn) unknown (SAGE PUBLICATIONS INC, 2021)
This study was conducted to determine the symptoms experienced by women at home and self-care agency after breast-conserving surgery. The study was carried out in a public hospital in Istanbul between January and June 2018. The sample of the study consisted of 65 women. The data were collected through face-to-face interviews using Patient Description Form, Symptom Check List and Self-Care Agency Scale during outpatient check-ups in the first and third weeks following discharge. The mean age of the women was 52.68 +/- 13.24. Fatigue, weakness, pain and insomnia were mostly experienced symptoms in the first and third weeks after discharge while fever, discharge from the wound area and nausea-vomiting symptoms were the least experienced symptoms in these weeks. It was determined that women had moderate self-care agency in the first and third weeks of discharge. Women who were married and whose income was equal to their expenses had higher self-care agency, and those living alone had lower self-care agency than those living with their spouses and children (p < 0.05). The self-care agency scores of those who did not have a chronic disease were higher than those with chronic diseases (p < 0.05). It is found that women with breast-conserving surgery experience symptoms related to the operation in the first and third weeks of discharge. Women's self care agency was moderate during the follow up period, meaning that these patients should be supported by nurses with regard to self care agency and symptoms experienced at home.
Keywords: breast cancer; breast conserving surgery; home-based monitoring; nursing; self-care agency; symptoms; CANCER